In-Vitro and Ex-Vivo Evaluation of Transfersomal Gel of Methotrexate - Chetna Modi; Praful Bharadia (Universidade de São Paulo, 2023)
Abstract Methotrexate on its oral and intravenous administration results in unwanted adverse effects. This drawback can be overcome by transdermal delivery because of its painless objective for systemic drug administration. Transfersomes are ultra-deformable vesicles with the flexibility to reach deeper tissues of the skin. The objective of this research work was to develop methotrexate transfersomal gel by thin film hydration technique, evaluated for entrapment efficiency, deformability, mean vesicle size, and stability, and incorporated into carbopol gel for ease of handling and skin applicability for a longer period of retention on skin. MTX-TFS gel & conventional gel were characterized for consistency, transparency, viscosity, and pH. Ex-vivo skin permeation studies were performed using abdominal goat skin and drug release kinetic parameters and transdermal flux were calculated using mathematical models. The results indicate that MTX was successfully entrapped (84.77 ± 2.35 %w/w) in transfersomes having 240±1.6 nm vesicle sizes and 27.13±0.7 deformability index. The gel was permeated through the skin at a rate of 28.12±2.58 µg/cm2/hr as compared to the conventional gel (10.35±2.14 µg/cm2/ hr). From the study, it was concluded that the MTX-TFS gel can be used as a possible substitute for the conventional formulation for transdermal drug delivery due to 3 times improvement in transdermal flux.